PENGATURAN DALAM UNDANG-UNDANG HAK POLITIK MANTAN TERPIDANA KASUS TINDAK PIDANA KORUPSI SEBAGAI CALON ANGGOTA LEGISLATIF PADA PEMILIHAN UMUM TAHUN 2019 - Hamidi Hamidi (UNES Law Review, 2020)
General election is a means of democracy that is used to elect people's representatives to sit as legislative members in the MPR, DPR, DPD and DPRD. The election was conducted in accordance with Article 2 paragraph (1) of the 1945 Constitution. The 2019 election was also attended by former convicted corruption cases. This is in accordance with PKPU rules Number 20 of 2018. With this decision, an extra-judicial polemic arises which is appropriate and important to be studied more specifically and academically. The formulation of the problem in this research is, How to regulate the political rights of former convicted corruption cases as legislative candidates in the 2019 general election? What are the implications of regulating the political rights of former convicts of corruption as a candidate for legislative members in the 2019 General Elections on Human Rights? The specification of this research is normative juridical research, which is a form of research that aims to describe the applicable laws and regulations, linked to legal theories and practice of positive law enforcement, which will later be linked to the problems examined in this scientific paper. Based on the results of the analysis, answers can be obtained: 1) The Political Rights Regulation of Former Convicted Corruption Crime Cases as Legislative Candidates in the General Election Year contradicts a higher law because based on the mandate of article 4 paragraph (3) Number 20 of 2018 concerning Election Commission Regulations General as well as article 240 paragraph (1) letter (g) of Law Number 7 of 2017 concerning General Elections. Article 28 letter d of the 1945 Constitution of the Republic of Indonesia. 2) Implications of regulating the political rights of former convicted corruption cases as candidates for legislative members in the 2019 general election against human rights, revocation of political rights for convicted corruption cases by human rights law activists (HAM) is of the view that deprivation of political rights is a violation of human rights. This is still debatable, because every sentence is basically a violation of human rights, but the violation is allowed, as long as it is based on the law.